Integrating resilience with functional ecosystem measures: A novel paradigm for management decisions under multiple‐stressor interplay in freshwater ecosystems. (18th May 2021) - Jaiswal, Deepa; Pandey, Usha; Mishra, Vibha; Pandey, Jitendra
Abstract: Moving beyond monitoring the state of water quality to understanding how the sensitive ecosystems "respond" to complex interplay of climatic and anthropogenic perturbations, and eventually the mechanisms that underpin alterations leading to transitional shifts is crucial for managing freshwater resources. The multiple disturbance dynamics—a single disturbance as opposed to multiple disturbances for recovery and other atrocities—alter aquatic ecosystem in multiple ways, yet the global models lack representation of key processes and feedbacks, impeding potential management decisions. Here, the procedure we have embarked for what is known about the biogeochemical and ecological functions in freshwaters in context of ecosystem resilience, feedbacks, stressors synergies, and compensatory dynamics, is highly relevant for process‐based ecosystem models and for developing a novel paradigm toward potential management decisions. This review advocates the need for a more aggressive approach with improved understanding of changes in key ecosystem processes and mechanistic links thereof, regulating resilience and compensatory dynamics concordant with climate and anthropogenic perturbations across a wide range of spatio‐temporal scales. This has relevance contexting climate change and anthropogenic pressures for developing proactive and adaptive management strategies for safeguarding freshwater resources and services they provide. Abstract : Impacts of anthropogenic drivers are evident on water quality change worldwide, yet the collateral/synergetic ecosystem effects induced by multiple stressors interplay in freshwater ecosystems remain unpredictable. This review presents a novel synthesis fostering new grounds for essential ways to not only evaluating the aquatic ecosystems but also acquiring knowledge in the mechanisms that underpin resilience and adaptive capacity of water resources dynamism and sustainable management of ecosystem change. These are necessary more especially under continued multifaceted anthropogenic‐climate‐environmental impacts.